Enzyme responsive GAG-based natural-synthetic hybrid hydrogel for tunable growth factor delivery and stem cell differentiation. (May 2016) - Anjum, Fraz; Lienemann, Philipp S.; Metzger, Stéphanie; Biernaskie, Jeff; Kallos, Michael S.; Ehrbar, Martin
Abstract: We describe an enzymatically formed chondroitin sulfate (CS) and poly(ethylene glycol) (PEG) based hybrid hydrogel system, which by tuning the architecture and composition of modular building blocks, allows the application-specific tailoring of growth factor delivery and cellular responses. CS, a negatively charged sulfate-rich glycosaminoglycan of the extracellular matrix (ECM), known for its growth factor binding and stem cell regulatory functions, is used as a starting material for the engineering of this biomimetic materials platform. The functionalization of CS with transglutaminase factor XIII specific substrate sequences is utilized to allow cross-linking of CS with previously described fibrin-mimetic TG-PEG hydrogel precursors. We show that the hydrogel network properties can be tuned by varying the degree of functionalization of CS as well as the ratio and concentrations of PEG and CS precursors. Taking advantage of TG-PEG hydrogel, compatible tagged bio-functional building blocks, including RGD peptides or matrix metalloproteinase sensitive domains, can be incorporated on demand allowing the three-dimensional culture and expansion of human bone marrow mesenchymal stem cells (BM-MSCs). The binding of bone morphogenetic protein-2 (BMP-2) in a CS concentration dependent manner and the BMP-2 release mediated osteogenic differentiation of BM-MSCs indicate the potential of CS-PEG hybrid hydrogels to promote regeneration of bone tissue. Their modular design allows facile incorporation of additional signaling elements, rendering CS-PEG hydrogels a highly flexible platform with potential for multiple biomedical applications.